Kontribusi Sosial Melalui Program Pertukaran Mahasiswa Merdeka 3 Di Desa Rindu Hati - Dzaky Isyuniandri; Mihbub Alam (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
This service explains the activities of the Student Exchange Program 3. PMM 3 is a one-semester domestic exchange program that will provide the experience of studying at the best universities throughout Indonesia, apart from that it will provide experience of getting to know diversity, honing leadership skills, building networks during college. , with the Nusantara Module activities, one of which is Social Contribution, social contribution is the final series of PMM 3 in 2023. We carry out social contributions in Rindu Hati Village, Kec. Taba Penanjung, Kab. Central Bengkulu, Prov. Bengkulu. The activities we carry out are divided into 3 fields, namely 1. Education, 2. Health, and 3. Tourism Village. And the results of this social contribution activity are being able to help free medical treatment, help teach at SDN 08 Central Bengkulu, provide books as learning media, and develop tourist attractions into tourist villages.